Keterampilan Mahasiswa Calon Guru Biologi dalam Menerapkan Kurikulum Merdeka Berdasarkan Pengembangan Perangkat Pembelajaran - Putri Agustina; Rina Astuti; Lina Agustina (Universitas Sebelas Maret, 2025)
Decree of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 56/M/2022 concerning Guidelines for Implementing Curriculum in the Context of Learning Recovery states that in order to recover learning loss that occurs in particular conditions, educational units need to develop a curriculum with The principle of diversification by the conditions of the educational unit, regional potential, and students, one of which is by implementing an independent curriculum. One of the characteristics of the independent curriculum that differentiates it from the previous curriculum is the development stage of learning tools. LPTK managers, including FKIP UMS, responded to this policy quickly. FKIP UMS, through the integrated learning laboratory, has begun implementing obligations for Biology student teacher candidates to develop independent curriculum learning tools in the 2021/2022 academic year. This research aims to analyze the abilities of prospective Biology teacher students in developing independent curriculum learning tools for the T.A. 2023/2024 microteaching course. The subjects of this research were P.S. P. Biology students at FKIP UMS who were taking microteaching courses in the even semester of F.Y. 2023/2024. Research parameters include students' abilities in developing teaching modules, student worksheets, and assessment instruments. Data analysis was carried out descriptively and qualitatively using percentage techniques. Based on the results of data analysis, in general, the ability of Biology teacher candidates at FKIP UMS to develop independent curriculum learning tools in the T.A. 2023/2024 microteaching course is in a suitable category with an average percentage of 69.4%. Let us look at the scores for each aspect. The average achievement of the student ability aspect in developing independent curriculum teaching modules is in the excellent category (74.3%). In comparison, the student ability aspect in developing independent curriculum assessment instruments is quite good (64.5%).